A framework to integrate design knowledge reuse and requirements management in engineering design - Baxter, David; Gao, James X.; Case, K.; Harding, J.; Young, R.; Cochrane, Sean; Dani, S. (Elsevier Science B.V., Amsterdam., 2008)
This paper presents a framework to integrate requirements management and design knowledge reuse. The research approach begins with a literature review in design reuse and requirements management to identify appropriate methods within each domain. A framework is proposed based on the identified requirements. The framework is then demonstrated using a case study example: vacuum pump design. Requirements are presented as a component of the integrated design knowledge framework. The proposed framework enables the application of requirements management as a dynamic process, including capture, analysis and recording of requirements. It takes account of the evolving requirements and the dynamic nature of the interaction between requirements and product structure through the various stages of product development. (C) 2007 Elsevier Ltd. All rights reserved.